<h3>(-3j²k³)²(2j²k)³</h3>
(-3j²k³)²(2j²k)³ = <em>When a power is raised to a power the exponents have to be multiplied.</em>
= (-3²j⁽²*²⁾k⁽³*²⁾)(2³j⁽²*³⁾k³) = <em>We can take out the constants</em>
= (9)(8)(j⁴k⁶)(j⁶k³) = <em>We can group the same variables</em>
= 72(j⁴j⁶)(k⁶k³) = <em>When multiplying two powers that have the same base, you have to add the exponents.</em>
= 72 j⁽⁴⁺⁶⁾k⁽⁶⁺³⁾ = 72j¹⁰k⁹
Answer = 72j¹⁰k⁹
Hope this helps!
Answer:
wag po kayo mag bibigay ng points na marami
Kasi ma iiscam po kayo
Answer:
-15
Step-by-step explanation:
-3(-4-5x)= -18
12+15x= -18-12
15x= -30
x= -30÷15
x= -15
Answer:
I can help!!!
Step-by-step explanation: